Building brand identity for sustainability of new emerging enterprises (a case study of bumiputera small fashion enterprises in Malaysia) / Siti Fatimah Hashim - Hashim, Siti Fatimah (2016)
Brand identity takes an aspirational perspective on ‘what’ and ‘who’ Bumiputera new emerging fashion (BNEF) enterprises in the market while emphasizing on the needs for sustainability. The increasing numbers of BNEF enterprises that hardly survive in the dynamic business environment and the rising roles of active consumers online and offline in Malaysia context have taken a toll even though have been supported by the government in so many ways. Thus, using brand identity building as a strategic tool for BNEF enterprises’ sustainability is an exploratory study that well described as the independent variable: Internal Elements which consist of Corporate Identity and Organizational Identity and External Elements which consist of Corporate Image and Reputation resulting Brand Loyalty as dependent variable. The conceptual framework therefore, significantly creates Brand Awareness and thus, develop Brand Loyalty for the sustainability of BNEF enterprises in the market. This research study seeks to the advancement of establishing the conceptualization of brand identity building by proposing brand identity as dynamic and strategic tools constructed by influencing inputs from top management, stakeholders and loyal customers. Hence, the research study proposes an innovative managerial framework together with the alignment of Strategic Stars of Brand Identity (Hatch & Schultz, 2001) in order to challenge the establishment approach of brand identity building specifically for sustainability of BNEF enterprises in Malaysia.